Рослинний покрив ботаніко-географічної ділянки “Кавказ” Національного ботанічного саду ім. М.М. Гришка НАН України. Повідомлення 2. Експозиційні виділи - Shynder, O.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2015)
Results of a comparative study of the structure of artificial plant community on phyto-geographical plot “Caucasus” ot National Botanical Garden of the NAS of Ukraine are presented. There are 8 main exposition sections of deciduous forests vegetation, 2 – coniferous forests, 2 – meadow and 1 – steppe are formed. A small area ecotone shrub vegetation and ornamental dendrologic group also is presented. This is a result of long research work on plant introduction from Caucasus in conditions of Kyiv. Floristic structure formed ex situ plant communities in the area are first investigated and described. In a culture in plant communities more fewer species is observing than in the nature of the Caucasus. Also, the degree of cultural formation of plant communities is somewhat different. These degree from degradation to slow expansion observed. The most artificial plant communities are mature and permanent. They are complete design model of plant communities of the Caucasus. Comprehensive study of cultural plant communities can improve the quality of plant introduction.